Knowledge, Attitude And Practice Towards Routine Medical Examination Among University Lecturers In Rivers State - Abigo, Ene Emilia; Okpako, J. E. F. (Advances in Social Sciences Research Journal, 2021)
The study examined the knowledge, attitude and practice of routine medical examination among university lecturers in Rivers State. A descriptive survey research design was adopted. The sample size consisted of 381 (12% of the total population) on a random sampling technique. Three research questions guided the study. A self-structured instruments titled “Knowledge Attitude and Practice of Routine Medical Examination Scale (KAPRME), Cronbach Alpha value of 0.78 was obtained for the content reliability. Simple percentage, Mean and standard deviation were used to analyse research questions. Findings showed that University Lecturers in Rivers State have knowledge and positive attitude on Routine Medical Examination. But, there is low level of practice for routine medical examination among the universities lecturers in Rivers State. Based on the findings, it was concluded that lecturers are aware of the impact of Routine Medical Examination but most times claim to be task-oriented taking for granted the nitty-gritty of life to be healthy. It was recommended that University administrators vis-à-vis individual lecturers should place optimum priority to Routine Medical Examination at least twice a year.